Are Alzheimer's and coronary artery diseases genetically related to longevity? - Bellou, Eftychia; Escott-Price, Valentina (Frontiers in Psychiatry, 2023)
In the last decade researchers have attempted to investigate the shared genetic architecture of longevity and age-related diseases and assess whether the increased longevity in certain people is due to protective alleles in the risk genes for a particular condition or whether there are specific “longevity” genes increasing the lifespan independently of age-related conditions’ risk genes. The aim of this study was to investigate the shared genetic component between longevity and two age-related conditions. For this purpose, we performed a cross-trait meta-analysis of publicly available genome-wide data for Alzheimer’s disease, coronary artery disease and longevity using a subset-based approach provided by the R package ASSET. Despite the lack of strong genetic correlation between longevity and the two diseases, we identified 38 genome-wide significant lead SNPs across 22 independent genomic loci. Of them 6 were found to be potentially shared among the three traits mapping to genes including DAB2IP, DNM2, FCHO1, CLPTM1 and SNRPD2. We also identified 19 novel genome-wide associations for the individual traits in this study. Functional annotations and biological pathway enrichment analyses suggested that pleiotropic variants are involved in clathrin-mediated endocytosis and plasma lipoprotein and neurotransmitter clearance processes. In summary, we have been able to advance in the knowledge of the genetic overlap existing among longevity and the two most common age-related disorders.